Parameter optimization of tuned mass damper for three-degree-of-freedom vibration systems - Khang, Nguyen Van; Loc, Trieu Quoc; Tuan, Nguyen Anh (Vietnam Journal of Mechanics, 2013)
There are problems in mechanical, structural and aerospace engineering that can be formulated as Nonlinear Programming. In this paper, the problem of parameters optimization of tuned mass damper for three-degree-of-freedom vibration systems is investigated using sequential quadratic programming method. The objective is to minimize the extreme vibration amplitude of vibration models. It is shown that the constrained formulation, that includes lower and upper bounds on the updating parameters in the form of inequality constraints, is important for obtaining a correct updated model.